2014
DOI: 10.15662/ijareeie.2014.0307055
|View full text |Cite
|
Sign up to set email alerts
|

Low Power LFM Pulse Compression RADAR with Sidelobe suppression

Abstract: ABSTRACT:One of the parameters of the pulsed RADAR that contributes range capability is the average power of the transmitter. The average power can be increased by increasing the peak power or transmitted pulse width or both. The complexity in the design of transmitter components to withstand high peak power is the most challenging task. On the other hand larger transmitted pulse width affects the RADAR capability to detect and track lower range targets. Maximum detection range of RADAR is increased by larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…There are many window techniques used in side lobe elimination or reduction such as Hamming, Hanning, Flattop, and Blackman windowing filter. In [12], it is illustrated that, Hamming windowing has a better performance among the above filter techniques according to resolution and peak of side lobe level.…”
Section: Fig 1 Matched Filter Components In the Frequency Domain [10]mentioning
confidence: 99%
“…There are many window techniques used in side lobe elimination or reduction such as Hamming, Hanning, Flattop, and Blackman windowing filter. In [12], it is illustrated that, Hamming windowing has a better performance among the above filter techniques according to resolution and peak of side lobe level.…”
Section: Fig 1 Matched Filter Components In the Frequency Domain [10]mentioning
confidence: 99%
“…There are many windowing techniques used in sidelobe elimination or reduction such as Hamming, Hanning, Flattop, and Blackman windowing filters. It has been shown that Hamming windowing has a better performance among other mentioned filter techniques put on the expense of resolution and peak of sidelobe level [5][6][7][8].…”
Section: Matched Filter Responsementioning
confidence: 99%
“…PSLR of LFM MF and OPT filter5. Proposed Sar Algorithm Flow Chart And Simulation ResultsAs shown in figure(5) flow charts (a) Range Doppler algorithm (b) Proposed algorithm using optimum filter. Generation of raw data is done with the block diagram shown in figure (6) of airborne-SAR simulation.…”
mentioning
confidence: 99%
“…The FFT computation takes on the signal as periodic or repeats itself for each block of data. If the signal is non-periodic, it results in the leakage in frequency spectrum of the signal causing the spectrum to spread out over a wide frequency range which arise difficulty in identifying the exact frequency content of the measured signal [7]. So window function is employed to reduce the leakage factor.…”
Section: Introductionmentioning
confidence: 99%
“…So window function is employed to reduce the leakage factor. When a window function is multiplied to a non periodic signal it makes the signal to be periodic and suppress the side lobes to a certain extent [7]. Window weighting can be applied both in time/frequency domain, the former method is preferred to later as it produces low PSLR values [8].…”
Section: Introductionmentioning
confidence: 99%